Urban planning and its impact in Strengthening healthy physical activity in urban Environments - سليمان أحمد عبد الكريم (Journal of Architecture and environment of child, 2021)
This study aimed to clarify urban planning interventions to promote healthy physical activity, and to formulate some proposals on disseminating a culture of healthy walking. The problem of the study lies in the wide spread of physical inactivity phenomenon considering the shortage in spaces for walking in many urban environments, especially in Arab countries. The study relies on the analytical descriptive approach. A brief description is given to the most prominent pedestrian spaces in the cities of Khartoum (Sudan) and Alkhobar (KSA). Of the study recommendations: The prevalence of phenomena that impede pedestrian movement in the study area in the city of Khartoum is due to a clear defect in the implementation of the guidelines for previous plans, including the current structural plan (2008-2033). And that the use of bicycles as a physical activity is still not common among residents of Al Khobar. Among the recommendations of the study: To provide digital devices for monitoring air quality to be installed at entrances to different walking spaces; and to give the population real-time information about weather conditions and air quality.